Human Flt3L generates dendritic cells from canine peripheral blood precursors: implications for a dog glioma clinical trial. - Weidong Xiong; Marianela Candolfi; Chunyan Liu; A K M Ghulam Muhammad; Kader Yagiz; Mariana Puntel; Peter F Moore; Julie Avalos; John D Young; Dorothy Khan; Randy Donelson; G Elizabeth Pluhar; et al. (PLoS ONE, 2010)
Glioblastoma multiforme (GBM) is the most common primary brain tumor in adults and carries a dismal prognosis. We have developed a conditional cytotoxic/immunotherapeutic approach using adenoviral vectors (Ads) encoding the immunostimulatory cytokine, human soluble fms-like tyrosine kinase 3 ligand (hsFlt3L) and the conditional cytotoxic molecule, i.e., Herpes Simplex Type 1- thymide kinase (TK). This therapy triggers an anti-tumor immune response that leads to tumor regression and anti-tumor immunological memory in intracranial rodent cancer models. We aim to test the efficacy of this immunotherapy in dogs bearing spontaneous GBM. In view of the controversy regarding the effect of human cytokines on dog immune cells, and considering that the efficacy of this treatment depends on hsFlt3L-stimulated dendritic cells (DCs), in the present work we tested the ability of Ad-encoded hsFlt3L to generate DCs from dog peripheral blood and compared its effects with canine IL-4 and GM-CSF.Our results demonstrate that hsFlT3L expressed form an Ad vector, generated DCs from peripheral blood cultures with very similar morphological and phenotypic characteristics to canine IL-4 and GM-CSF-cultured DCs. These include phagocytic activity and expression of CD11c, MHCII, CD80 and CD14. Maturation of DCs cultured under both conditions resulted in increased secretion of IL-6, TNF-alpha and IFN-gamma. Importantly, hsFlt3L-derived antigen presenting cells showed allostimulatory potential highlighting their ability to present antigen to T cells and elicit their proliferation.These results demonstrate that hsFlt3L induces the proliferation of canine DCs and support its use in upcoming clinical trials for canine GBM. Our data further support the translation of hsFlt3L to be used for dendritic cells' vaccination and gene therapeutic approaches from rodent models to canine patients and its future implementation in human clinical trials.